Hipertensi dan Komplikasi Yang Menyertai Hipertensi - Farid Husaini; Tischa Rahayu Fonna (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Hypertension is a condition in which the blood pressure in the systemic arteries remains consistently high. Blood pressure is generally measured as the result of systolic blood pressure (pressure when the heart contracts and delivers blood to the arteries) and diastolic blood pressure (pressure when the heart relaxes). The threshold for diagnosing hypertension varies depending on the measurement method used. Hypertension is often referred to as the